Homozygous familial hypercholesterolemia with severe involvement of the aortic valve—A sibling‐controlled case study on the efficacy of lipoprotein apheresis. Issue 3 (12th March 2020) - Galiano, Matthias; Hammersen, Johanna; Sauerstein, Katja; Blessing, Holger; Rümmele, Petra; Purbojo, Ariawan; Schöber, Martin; Moosmann, Julia; Raffelsbauer, Gunter; Heibges, Andreas; Klingel, Reinhard
Abstract: Background: Homozygous familial hypercholesterolemia (hoFH) can cause severe atherosclerotic cardiovascular disease (ASCVD) in early infancy. Diagnosis and initiation of effective lipid‐lowering therapy (LLT) are recommended as early as possible to prevent ASCVD‐related morbidity and mortality. Methods: The clinical courses of a pair of siblings with an identical hoFH genotype, who exhibited major similarities of their clinical phenotype were analyzed in a case‐control fashion including the family. Results: The older sibling was diagnosed with hoFH at the age of 4. Untreated LDL‐cholesterol (LDL‐C) was 17 mmol/L (660 mg/dL). LLT including lipoprotein apheresis (LA) was initiated and has been successful for 8 years now. A reduction of estimated cholesterol burden by 74% was achieved by LA and combined drug therapy including statins and ezetimibe. The efficacy of escalation of drug therapy was limited because the underlying LDL receptor (LDLR) mutation in the family resulted in substantially reduced receptor function. Treatment with proprotein convertase subtilisin‐kexin type 9 (PCSK9)‐antibodies failed. His younger brother died at the age of 2 years shortly after the hoFH diagnosis of the elder sibling. Postmortem examination revealed advanced aortic root atheroma and aortic valve stenosis. In the older sibling, aortic valve stenosis and insufficiency were treated at the age of 9 years with mechanical aortic valve replacement. Conclusions: LLT including LA should be initiated as early as possible following the diagnosis of hoFH with very high LDL‐C levels. With the same genotype, the phenotype of hoFH can exhibit similar patterns but outcome is substantially related to treatment.